A Confirmation of the Dinosaur Ancestry of Humans Found in Dog DNA Analysis - Pirot, Florent (European Journal of Applied Sciences, 2021)
This letter confirms the dog DNA study of a team of researchers published last year by crossing with the findings published by the author of this letter very recently. Both results were achieved independently (the author of this letter had no knowledge of the team's results). It also makes a suggestion to explain the results on the unidirectional DNA transfer from dogs to wolves that is one of the team's key findings.